2018
DOI: 10.1638/2016-0299r2.1
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of a Novel Sustained-Release Ivermectin Varnish for Treatment of Wound Myiasis in Zoo-Housed Animals

Abstract: Myiasis is a major disease condition in human and veterinary medicine. Domestic, free-ranging, and zoo-housed animals can be severely affected by myiasis. Depending on case severity, multiple treatment episodes may be indicated and can lead to recurrent capturing, handling stress, and anesthetics, all of which increase the risk of adverse responses (including death) individually and also in the herd. As an insecticide, ivermectin is often used for larval control. A total of 28 individual myiasis cases were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Drugs requiring repeated administration are a major hindrance in wildlife medicine and have resulted in the development of delivery systems that significantly extend action (Avni-Magen et al, 2018). For example, replacing frequent subcutaneous ivermectin, a topical ivermectin sustained-release varnish was an efficacious single-dose treatment for myiasis in zoo-housed wildlife, including ungulate and avian species (Avni-Magen et al, 2018). Hydrogels, a group of gel-forming delivery systems, also show promise for prolonging therapeutic action, increasing efficacy and reducing toxicity (Coutant et al, 2019).…”
Section: Therapeutic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs requiring repeated administration are a major hindrance in wildlife medicine and have resulted in the development of delivery systems that significantly extend action (Avni-Magen et al, 2018). For example, replacing frequent subcutaneous ivermectin, a topical ivermectin sustained-release varnish was an efficacious single-dose treatment for myiasis in zoo-housed wildlife, including ungulate and avian species (Avni-Magen et al, 2018). Hydrogels, a group of gel-forming delivery systems, also show promise for prolonging therapeutic action, increasing efficacy and reducing toxicity (Coutant et al, 2019).…”
Section: Therapeutic Agentsmentioning
confidence: 99%
“…Improving the utility of existing PI agents by targeting their specific limitations is another pathway to success. Drugs requiring repeated administration are a major hindrance in wildlife medicine and have resulted in the development of delivery systems that significantly extend action (Avni‐Magen et al, 2018). For example, replacing frequent subcutaneous ivermectin, a topical ivermectin sustained‐release varnish was an efficacious single‐dose treatment for myiasis in zoo‐housed wildlife, including ungulate and avian species (Avni‐Magen et al, 2018).…”
Section: Directions For Pharmacological Interventionsmentioning
confidence: 99%
“…The varnish was applied from one to three days, with complete resolution of the lesions. More recently, efficacy of ivermectin varnish in the treatment of wound myiasis of various severity was assessed in a variety of zoo animals, and it has been demonstrated that the use of a topical ivermectin varnish (with or without concurrent injectable ivermectin) can reduce handling and treatments, had no detectable adverse effects, and had minimal recurrence of the disease when compared with cases treated without it ( Avni-Magen et al., 2018 ).…”
Section: Non-bioavailable Topical Devicesmentioning
confidence: 99%
“…It acts by causing the parasite's cell membrane to increase in permeability resulting in paralysis and death 24 . It has been widely used in cases of animal myiasis successfully 25 . In our study, we used local antiseptics, turpentine oil over the umbilicus as a repellent for larva, manually removed the larva and injectable antibiotics were given to avoid sepsis.…”
Section: Picture Of Maggots At the Time Of Dischargementioning
confidence: 99%